2012
DOI: 10.1093/ntr/nts112
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Alcoholic Smokers, Nonsmokers, and Former Smokers: Personality, Negative Affect, Alcohol Involvement, and Treatment Participation

Abstract: Introduction: Previous research has indicated that smoking behavior in the general population is linked to personality traits such as behavioral undercontrol and negative emotionality, but it is unknown whether these traits pertain to alcoholic smokers. Further, prior research has not established whether alcoholic smokers differ from their nonsmoking counterparts in terms of alcohol involvement severity and treatment participation. Exploration of these associations is important, given the high prevalence of ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
1
7
1
Order By: Relevance
“…We might hypothesize that conditions such as the rapid disease course (early onset of alcohol abuse), the history of externalizing behaviors, and the probable familiarity with drug treatment centers may explain why these patients have a need to seek medical treatment for alcohol dependence earlier than other phenotypes. Studies report that this type of clinical profi le seems to interfere in the development, duration, adherence, and prognosis of alcohol use disorder treatment even aft er controlling for distinct behavioral/personality traits, psychiatric comorbidities, and cognitive disabilities (Walitzer and Dearing 2013;Ibabe et al 2014). Poor compliance to treatment in Cloninger type II patients was also observed in research (von Knorring et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…We might hypothesize that conditions such as the rapid disease course (early onset of alcohol abuse), the history of externalizing behaviors, and the probable familiarity with drug treatment centers may explain why these patients have a need to seek medical treatment for alcohol dependence earlier than other phenotypes. Studies report that this type of clinical profi le seems to interfere in the development, duration, adherence, and prognosis of alcohol use disorder treatment even aft er controlling for distinct behavioral/personality traits, psychiatric comorbidities, and cognitive disabilities (Walitzer and Dearing 2013;Ibabe et al 2014). Poor compliance to treatment in Cloninger type II patients was also observed in research (von Knorring et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…For example, data exist suggesting that alcohol treatment seekers who smoke may exhibit a greater severity of alcohol problems and dependence relative to those who do not smoke (e.g., Walitzer & Dearing, 2012). This finding appears to be attributable to negative synergistic effects between nicotine and ethanol (Campbell, Taylor, & Tizabi, 2006; Lapin, Maker, & Bhardwaj, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown smoking to have a negative association with alcohol treatment participation (Satre, Kohn, & Weisner, 2007; Walitzer & Dearing, 2012) and alcohol treatment outcome (Hintz & Mann, 2007; Kohn, Tsoh, & Weisner, 2003; Mason & Lehert, 2009; Satre et al, 2007). In terms of alcohol treatment participation, Walitzer and Dearing (2012) compared alcohol outpatient smokers, non-smokers, and former smokers in a controlled trial that included 12 sessions of outpatient alcohol treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common type of polydrug use is alcohol and tobacco taken in concert [11,12]. The magnitude of tobacco smoking is extremely high among alcoholics [13] and is drastically higher than the rate in the general population [14,15]. Those who smoke are ten times more likely to be alcoholics than those who do not [16].…”
Section: Introductionmentioning
confidence: 99%